Pemanfaatan Rebung Sebagai Makanan Program Diet Yang Bernilai Ekonomis - Puji Muniarty; Della Saputri; Nur Fetiningsih Syaframis; Muhammad Arman Maulana; Rafiqa Zulianti; Siti Nur Alfisahr (Bulletin of Management and Business, 2021)
This study aims to determine the benefits of bamboo shoots as a diet program food that has economic value. The research method used is the library method. The use of bamboo shoots as food, a diet program can provide a long-lasting feeling of fullness because of its fiber content, so that the desire to eat can be controlled. Then bamboo shoots can be used as a support in a diet program with natural ingredients, because bamboo shoots have low sugar, protein and fat content. On the other hand, the use of bamboo shoots as a source of food for the diet program also provides economic benefits.